Quantum dot blueing and blinking enables fluorescence nanoscopy - Hoyer, Patrick; Staudt, Thorsten; Engelhardt, Johann; Hell, Stefan (Nano letters, 2011)
We demonstrate superresolution fluorescence imaging of cells using bioconjugated CdSe/ZnS quantum dot markers. Fluorescence blueing of quantum dot cores facilitates separation of blinking markers residing closer than the diffraction barrier. The high number of successively emitted photons enables ground state depletion microscopy followed by individual marker return with a resolving power of the size of a single dot (∼12 nm). Nanoscale imaging is feasible with a simple webcam.